Osservazioni bio-etologiche su Oberea erythrocephala Schrank ( Coleoptera, Cerambycidae, Lamiinae) (Bollettino di zoologia agraria e bachicoltura, 2024)
The Oberea erythrocephala Schrank ( Coleoptera, Cerambycidae) is a Lamiinae whose larvae develop in stems of herbaceous plants. This Oberea, whose host plant is Euphorbia cyparissias, has one annual generation. The adults appear in June; they feed on stems and leaves of Euphorbia, on which they also mate and lay their eggs. The female prepares a hole by gnawing the stem with mandibles and through this hole introduces one egg in the pith. Larva develops from June to autumn feeding on pith of stem and root; during this latter period it becomes mature. Larva passes the winter in the root, at ground level or just a little lower, in a cell closed above by a plug of shredded materia!. Pupa occurs in May. From mature larvae of Oberea erythrocephala the internal parasite Phaenolobus terebrator (Scop.) (Hym., Ichneumonidae) was reared.